2015
DOI: 10.1038/srep17827
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing analysis of the heterogeneity of seed and commercial lots of the bacillus Calmette-Guérin (BCG) tuberculosis vaccine substrain Tokyo-172

Abstract: BCG, only vaccine available to prevent tuberculosis, was established in the early 20th century by prolonged passaging of a virulent clinical strain of Mycobacterium bovis. BCG Tokyo-172, originally distributed within Japan in 1924, is one of the currently used reference substrains for the vaccine. Recently, this substrain was reported to contain two spontaneously arising, heterogeneous subpopulations (Types I and II). The proportions of the subpopulations changed over time in both distributed seed lots and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Previously, spontaneous heterogeneity of BCG seed lots and commercial vaccines during vaccine production determined by variant calling was analyzed in the Tokyo-172 vaccine strain [32]. In line with the published data, we observed a synonymous A2139G single nucleotide base substitution (position 3,175,529, "-" chain) in BOVR_15,090, i.e., the glnD (ortholog Rv2918c in M. tuberculosis H37Rv) gene, without Ala replacement in position 713 of 808 amino acids in the conservative domain of the PII uridylyltransferase protein in all genomes studied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, spontaneous heterogeneity of BCG seed lots and commercial vaccines during vaccine production determined by variant calling was analyzed in the Tokyo-172 vaccine strain [32]. In line with the published data, we observed a synonymous A2139G single nucleotide base substitution (position 3,175,529, "-" chain) in BOVR_15,090, i.e., the glnD (ortholog Rv2918c in M. tuberculosis H37Rv) gene, without Ala replacement in position 713 of 808 amino acids in the conservative domain of the PII uridylyltransferase protein in all genomes studied.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, allele G was recorded in the genomes of BCG str. Tokyo 172 which represents a well-defined Type I subpopulation of BCG Tokyo-172, the closest to BCG Russia (GenBank: NZ_CUWO01000001) and Russia ATCC 35740, members of presumably monophyletic "early" substrain group of BCG [10,30,32]. The G variant was also common in the reference sequences of some other BCG strains, e.g., Pasteur 1173P2, Danish 1331, ATCC 35743 (Tice), Moreau RDJ, used worldwide for vaccine production and research purposes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It belongs to early strains and is one of the most widely used strains in the world ( 2 ). Though most of the described differences among BCG strains refer to the period before the worldwide use of lyophilized vaccine, Wada et al ( 3 ) have shown that mutations in vaccine strains obtained by various vaccine manufacturers from a single cell source over time reach detectable levels. Because of that, whole-genome sequencing and comparison of all BCG Russia strains are extremely important.…”
Section: Genome Announcementmentioning
confidence: 99%